Possible Approaches to Primary Prevention of Cardiovascular Diseases - V. N. Larina; D. S. Mkrtychev; V. A. Kuznetsova; A. A. Tyazhelnikov (Рациональная фармакотерапия в кардиологии, 2020)
In recent years there is a positive trend in the development of preventive medicine, in particular, primary prevention of diseases. However, in most cases, patients seek help from a doctor after the manifestation of the disease, and therefore, early identification of risk factors (RF) remains relevant. Conduction of a large number of studies that are aimed at studying modifiable RF associated with the development of cardiovascular diseases (CVD), allowed the experts of the American Heart Association to develop recommendations “Life's Simple 7”, which makes it possible to structure methods of primary prevention of CVD and minimize the risk of their development. In 2019, experts from the American College of Cardiology presented a simplified version of these recommendations, to improve approaches to primary prevention and their effectiveness not only for doctors but also for patients. Thus, by involving the patient in the decision-making process about follow-up treatment, doctors can achieve a high level of compliance, which is essential for improving the prognosis. The “ABCDE” recommendations, in name of which are reflected the first letters of the leading CVD RF, include such paragraphs as RF assessment, the use of antiaggregating therapy, correction of blood pressure, cholesterol levels, smoking elimination, correction of high glucose levels and diabetes treatment, weight loss, assessment of social and economic factors affecting the morbidity in a particular patient. Despite the undoubted benefit of the “ABCDE” recommendations, some problems of primary prevention currently cannot be solved: the inability to accurately assess social and economic RF; the imperfection of the used CVD risk scales. The updated version of the recommendations allows not only to assess the existing RF of the patient, but also to effectively correct them. In addition, the patient himself can read the recommendations, which improves understanding of the primary prevention importance.